2010
DOI: 10.1177/0892705710367978
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Behavior of Carbon/PEKK Thermoplastic Composite Tube Under Bending Load

Abstract: In an effort to develop thermoplastic composite tubes for helicopter landing gear applications, the mechanical behavior of straight tubes subjected to bending has been studied and presented here. It was found that interlaminar normal stresses of large values exist between layers located under the loading point. This can cause delamination between different layers at location under the loading point. The stiffness of the tube along the circumferential direction is important to prevent inward deformation under t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Poly(aryl ether ketone)s (PAEKs) are a family of high‐performance thermoplastics that offer excellent chemical and thermal resistance, good mechanical properties, and manufacturability into end‐use components for critical applications. They find widespread use in the medical, semiconductor manufacturing, aerospace, automotive and petrochemical industries. Poly(ether ether ketone) (PEEK) (Figure (a)) is the most widely available of the PAEK family, has the largest production volume, and performs well in most sealing and connector applications that involve contact with drilling fluids and sour (sulfur containing) crude oil under high‐pressure and high‐temperature conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(aryl ether ketone)s (PAEKs) are a family of high‐performance thermoplastics that offer excellent chemical and thermal resistance, good mechanical properties, and manufacturability into end‐use components for critical applications. They find widespread use in the medical, semiconductor manufacturing, aerospace, automotive and petrochemical industries. Poly(ether ether ketone) (PEEK) (Figure (a)) is the most widely available of the PAEK family, has the largest production volume, and performs well in most sealing and connector applications that involve contact with drilling fluids and sour (sulfur containing) crude oil under high‐pressure and high‐temperature conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the current simulation methodology is based on pure bending assumption. However, in Derisi et al 2,3 it was found that for composite tubes, the adjacent layers have complex interactions in three-point bending configuration, which is simply not the case for an aluminum structure. This might also be due to the effects of shear deformation, which would not show up in the predicted <EI> values.…”
Section: Discussionmentioning
confidence: 98%
“…In spite of these, the authors have developed a generic stacking sequence that enables a composite tube to match the flexural stiffness, load-bearing capability and energy absorption of a target aluminum tube via strategic location of the plies across the thickness. 2,3 Such tubes are called equivalent in this study. The equivalency in energy absorption imposes two conditions on the composite tube.…”
Section: Introductionmentioning
confidence: 99%
“…Bai et al [14] investigated the buckling behavior of thermoplastic pipes under combined bending and tension loads. Derisi et al [15] and Shadmehri et al [16] studied the composite tubes under bending. Effect of pressure, shear and torsion on anisotropic materials was analyzed by Ting [17,18].…”
Section: Introductionmentioning
confidence: 99%